Wage growth and inequality in urban China 1988-2013 - Björn Gustafsson; Haiyuan Wan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We investigate the evolution of wage levels, wage inequality, and wage determinants among urban residents in China using China Household Income Project data from 1988, 1995, 2002, 2007, and 2013. Average wage grew impressively between each pair of years. Wage inequality had long been on the increase, but between 2007 and 2013 no clear changes occurred. In 1988, age and wages were positively related throughout working life, but more recently older workers' wages have been lower than those of middle-aged workers. The relationship between education and wages was weak in 1988 but strengthened rapidly thereafter - a process that came to a halt in 2007. During the period in which China was a planned economy the gender wage gap was small in urban China, but it widened rapidly between 1995 and 2007. We also report the existence of a premium for being employed in a foreign-owned firm or in the state sector.
Keywords: J31; P23; P31; 330; wages; wage inequality; wage growth; wage functions; urban China; labour market